Addendum to “Treatment of Gamow states using tempered ultradistributions” - De Paoli, Ángel Luis (2000)
In Ref. [1] we showed that it is possible to extend analitically, and with the use of tempered ultradistributions, the pseudonorm defined by T. Berggren for Gamow states. In that reference we define this pseudonorm for all states determined by the zeros of the Jost function for any short range potential. However, the proof is not completely general due to the fact that the statement hl(0, r)=Cφl(0, r) is not true in all cases. In this addendum we give a new proof, general and independent of that statement.